Self-focusing effect on the second harmonic generation in the KDP single crystals with incorporated anatase nanoparticles - Gayvoronsky, V.Ya.; Kopylovsky, M.A.; Yatsyna, V.O.; Popov, A.S.; Kosinova, A.V.; Pritula, I.M. (Functional Materials, 2012)
Second harmonic generation efficiency versus the TiO₂ nanoparticles concentration incorporated in the KDP single crystals was studied within picosecond range pump pulses at 1064 nm. For the first time we have obtained the frequency conversion efficiency enhancement in the KDP:TiO₂ in comparison with the KDP crystals due to the internal self-focusing effect that was observed as the pump beam spatial profile narrowing at moderate peak intensities. Досліджено залежність ефективності генерації другої гармоніки від концентрації наночастинок TiO₂, інкорпорованих у монокристалічну матрицю KDP, при збудженні пікосекундними лазерними імпульсами на довжині хвилі 1064 нм. Вперше показано підсилення ефективності перетворення частоти випромінювання у монокристалах К0Р: TiO₂ у порівнянні з KDP завдяки ефекту внутрішнього самофокусування, що про являється у звуженні просторового профілю пучка накачки при помірних інтенсивностях збудження. Исследована зависимость эффективности генерации второй гармоники от концентрации наночастиц TiO₂, инкорпорированных в монокристалличсскую матрицу KDP, при возбуждении пикосекундными лазерными импульсами на длине волны 1064 нм. Впервые показано усиление эффективности преобразования частоты излучения в монокристаллах KDP:TiO₂ по сравнению с KDP благодаря эффекту внутренней самофокусировки, который проявляется в сужении пространственного профиля пучка накачки при умеренных интенсивностях возбуждения.